DIALOG BAKISAH (BIJAK KELOLA SAMPAH) : SAMPAH TANGGUNG JAWAB SIAPA? - Risanta, Muhammad; Adista Anjar Diany (Jurnal Abdi Masyarakat, 2025)
One of the main reasons for the lack of optimal waste management is the low level of public awareness about the importance of managing waste wisely and responsibly. Communication and education strategies that can reach the public widely and effectively are needed. One medium that has great potential in disseminating information and shaping public opinion is local radio. The target audience for this community service activity is all listeners of Radio Suara Banjar 100.4 FM or listeners via the Radio Suara Banjar streaming application. This activity uses a sharing session method packaged in a dialogue or talk show format. This method was chosen to facilitate the speakers in conveying issues related to waste in a communicative, light, and easy-to-understand manner for radio listeners. A very important approach in waste management is the application of the 3R principle, namely Reduce, Reuse, and Recycle. Discussions on waste sorting and waste banks were also included in this dialogue. This community service activity raised public awareness that waste is their own responsibility, and that good behavior in managing it can have a positive impact on humans, the environment, and future generations. Keywords: Waste management, Waste Bank, Reduce, Reuse, Recycle